Pancasila and Technogeopolitics: Integrating National Values into Foreign and Technology Policy - Permana, Aditya; Prasetyo, Ardian (Pancasila: Jurnal Keindonesiaan, 2025)
This paper investigates Indonesia’s challenges in the global techno-geopolitical order and the role of Pancasila as a normative foundation for foreign and technology policy. Existing analyses often reduce Indonesia’s strategy to pragmatic hedging amid U.S.-China rivalry. This study advances the debate by highlighting the tension between the rhetorical and substantive use of Pancasila. As rhetoric, Pancasila legitimizes existing choices (e.g. “hedging”) without addressing structural dependency. As substance, it provides an ethical paradigm that integrates justice, humanity, and sovereignty into digital governance. The paper demonstrates how Indonesia can move beyond pragmatist adaptation (Western liberal universalism, Chinese techno-statism, and competing Global South approaches, e.g. Brazil’s rights-based model and India’s growth-based strategy) toward normative entrepreneurship. The paper prescribes three steps: (1) operationalizing Pancasila values into measurable benchmarks, (2) reframing hedging as normative entrepreneurship, and (3) aligning domestic digital strategies with ethical commitments. The core contribution is to show that Indonesia’s global relevance hinges not merely on strategy, but on transforming Pancasila into a “substantive compass” for techno-diplomatic engagement, or as an approach that offers a distinct normative alternative in international debates on digital order.